Genotypic diversity and phenotypic traits of Streptococcus mutans isolates and their relation to severity of early childhood caries - Remberto Marcelo Argandoña Valdez; Cristiane Duque; Karina Sampaio Caiaffa; Vanessa Rodrigues dos Santos; Maria Luiza de Aguiar Loesch; Natalia Helena Colombo; Rodrigo Alex Arthur; Thais de Cássia Negrini; Marcelo Fabiano Gomes Boriollo; Alberto Carlos Botazzo Delbem (BMC, 2017)
Abstract Background Early childhood caries (ECC) is an aggressive condition that can affect teeth of young children. This study aimed to evaluate genotypic diversity and phenotypic traits of S. mutans isolated from dental biofilms of children with different caries status in comparison with caries free (CF) children. Methods Streptococcus mutans strains were isolated from supragingival biofilm samples of CF, ECC and severe-ECC (S-ECC) children and genotyped by arbitrary-primer polymerase chain reaction - AP-PCR. S. mutans genotypes were tested for their ability to reduce the suspension pH through glycolysis, to tolerate extreme acid challenge and by their ability to form biofilm. Response variables were analyzed by ANOVA/Tukey or Kruskal-Wallis/Mann-Whitney tests at a 5% of significance. Results There was an increase in the prevalence of Streptococcus mutans in biofilms with the severity of dental caries. No differences in genotypic diversity and in acidogenicity of genotypes were found among CF, ECC and S-ECC children. S mutans strains with genotypes more characteristic for ECC and S-ECC children formed more biofilms than those identified in CF children. The strains isolated from S-ECC children were highly acid tolerant. Conclusion Although S. mutans genotypic diversity was similar among the groups of children, phenotypic traits of S. mutans, especially the acid tolerance response, could explain the severity of early childhood caries.